Development of Interactive Game-Based Learning Media Using Realistic Approach to Improve Students' Mathematical Problem-Solvingin Social Arithmetic Materials for Grade VII - Qotrunada, Alisya; Furqon, Syamsul (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Students' mathematical problem-solvingare one of the basic skills in mathematics learning that must be possessed by every student. The low level of mathematical problem-solvingability of grade VII students at MTs Ma'arif NU 1 Pekuncen is the reason for the development of this learning media. The purpose of this study is to develop game-based interactive learning media using a realistic approach that is valid and effective in improving students' mathematical problem-solving in social arithmetic material in grade VII. This research uses the Research and Development (R&D) method. The results obtained in this study show that the interactive learning media of game-based learning is valid to be used with the acquisition of nasils by validation, namely the validation of the first and second experts obtained validity coefficients of 3.79 and 3.4, the practicality test by teachers obtained a validity coefficient of 3.8, and also the student response test with a score of 88.3. This learning media is also effectively used in improving students' mathematical problem-solving which is characterized by the average post-test of the experimental class of 75 which is greater than the average of the control class which gets a result of 59. Then, based on the post-test t-test, a significance of 0.000 was obtained, which was smaller than the limit of the significance level of 0.05. This indicates that the learning media developed is effectively used in improving students' mathematical problem-solving in social arithmetic material in class VII at MTs Ma'arif NU 1 Pekuncen.